Fall prevention education to reduce fall risk among community-dwelling older persons: a systematic review - Mei, Fong Ng; Soh, Kim Lam; Saimon, Rosalia; Wai, Myint Wai; Mortell, Manfred; Soh, Kim Geok (Wiley-Blackwell Publishing, 2021)
Objectives: This review aims to identify types of the existing fall prevention education (FPE) and their effectiveness in promoting fall risk awareness, knowledge and preventive fall behaviour change among community-dwelling older people. Background: FPE is a cost-effective and helpful tool for reducing fall occurrences. Evaluation: This is a systematic review study using electronic searches via EBSCOHost® platform, ScienceDirect, Scopus and Google Scholar in March 2021. The review protocol was registered with PROSPERO (CRD42021232102). The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement flow chart guided the search strategy. Articles published from January 2010 to March 2021 were included for quality appraisal using the 'Transparent Reporting of Evaluations with Non-randomised Designs' (TREND) and the 'Consolidated Standards of Reporting Trials' (CONSORT) statement for randomised controlled trial studies. Key issues: Six FPE studies selected emphasised on personal health status, exercise and environmental risk factors. These studies reported an increase in fall risk awareness or knowledge and a positive change in fall preventive behaviours. Two studies included nurses as educators in FPE. Conclusion: FPE evidently improved awareness or knowledge and preventive fall behaviour change among older adults. Nurses are in great potential in planning and providing FPE for older adults in community settings. Implications for nursing management: Expand nurses' roles in fall prevention programmes in community settings by using high-quality and evidence-based educational tools. Highlight the nurse's role and collaborative management in FPE.